The present state of Colombia 1827 ; containing an account of the principal events of its revolutionary war ; the expeditions fitted out in England to assist in its emacipation ; its constitution ; financial and commercial laws ; revenue expenditure and public debt ; agricultura ; mines ; mining and other associations ; with a map, exhibiting its mountains, rivers, departments, and provinces / by an Officer, Late in the Colombian Service (1827)
Chapter I. Introduction ; classification of colonies ; oppression of spanish colonies ; comparison between colonies of England and Spain ; attempts of Miranda ; revolution in Venezuela ; earthquake at Caracas ; death of Miranda ; revolutionary war ; Morillo ; his sanguinary conduct ; battles of Bargas and Boyacá ; armistice ; battle of Carabobo ; capture of Maracaybo ; Bolívar -- Chapter II : narrative of a Campaign ; english expeditions ; colonels hippisley, Macdonald, Wilson, Skene, Cambell, Gilmour, Elsom ; generals english, Macgregor, D´Evereux -- Chapter III : union of New Granada and Venezuela ; Republic of Colombia ; its constitution ; laws relative to comerce and finance ; encouragement to settlers ; agricultural company ; exclusive privileges ; steam-boats on the Magdalena ; the Orinoco ; the lake of Maracaybo ; sociedad emprendadora -- Chapter IV : territorial divisions of Colombia ; population of provinces ; congress ; army ; navy ; privateers ; Cuba ; foreign and domestic debt -- Chapter V : natural wealth of Colombia ; cordilleras ; their effect upon character of population ; and climate ; agriculture ; cacao ; coffee ; indigo ; cotton ; tobacco ; dyewoods ; rice ; sugar ; whet ; pastoral wealt ; cultivation of the vine ; obstructions to agricultural industry -- Chapter VI : mineral productions of Colombia ; gold ; silver ; platina ; mercury ; cooper ; lead ; iron ; coal ; rock-salt ; mining companies : Bolívar ; Colombian ; Carthagena ; and Anglo-Colombian ; pearl fishery ; conclusion